PERSPEKTIF KYAI HAJI BISRI MUSTHOFA TENTANG PENDIDIKAN ISLAM - Fahrul Hamu; Andi Bunyamin; Abd Rauf Assagaf; M. Hasibuddin; Ishaq Shamad; Surani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to explore and analyze the concept of Islamic education according to K.H. Bisri Mustofa, a charismatic Indonesian Muslim scholar and intellectual. The main focus of this research is to identify the basic concepts, objectives, and curriculum of Islamic education offered in his works, particularly in Tafsir Al-Ibriz. This research is a library research study using a descriptive-qualitative approach. Primary data were obtained from the written works of K.H. Bisri Mustofa, while secondary data were obtained from relevant supporting literature. The results of the study show that K.H. Bisri Mustofa's perspective on Islamic education is rooted in the traditional values of the pesantren (Islamic boarding school), combined with the spirit of contextualization with the times. According to him, Islamic education does not only focus on intellectual intelligence and mastery of classical Islamic texts (kitab kuning), but also emphasizes the formation of akhlakul karimah (noble character) and the independence of santri (students). The implications of this thought underline the importance of integrating spiritual, moral, and social aspects within the modern Islamic education system in order to produce a generation that is competent both religiously and socially.